Efek Ekstrak Metanol Daun Pucuk Merah Terhadap Kadar Glukosa Darah - Syari, Jajar Pramata (Jurnal Laboratorium Khatulistiwa, 2022)
Blood glucose level is the amount of glucose in the blood. High blood glucose levels can be lowered with traditional plants such as red shoots. The leaves of the red shoots are commonly used as herbal medicine as antibacterial, antioxidant and antidiabetic. The content of flavonoid compounds, alkaloids, saponins, tannins, polyphenols found in red shoots is known to have antidiabetic activity. The purpose of this study was to explain the effect of giving red shoots leaf extract on blood glucose levels. The method used is the enzymatic method with a glucometer. This research methodology is a Quasi Experimental Design. The population and samples in this study were male (Mus musculus) mice, 2-3 months old and weighing 20-30 grams with 3 treatments, namely 200 mg/kgBW, 400 mg/kgBW, 600 mg/kgBW. The results of the Simple Linear Regression test for a dose of 200 mg/kgBW, a dose of 400 mg/kgBW and a dose of 600 mg/kgBW obtained p value = 0.000 < 0.05 then Ha is accepted, which means that there is a significant effect between red shoot leaf extract on levels of blood glucose.